The Role of Marketing Technology Adoption on Farmers’ Economic Sustainability through Market Access as a Mediating Variable - Tri Sanatha Wahyu Akbar; Riani Winarni; Galih Raspati; Sri Rahayu; Dapit Suherman (Department of Management, Universitas PGRI Yogyakarta., 2026)
Purpose: This study aims to analyze the effect of marketing technology adoption on farmers’ economic sustainability and to examine the mediating role of market access in strengthening this relationship. Methodology: A quantitative descriptive–associative approach was employed using 330 farmers selected through the Isaac & Michael sampling table from a population of 6,563. Data were collected through structured questionnaires and analyzed using path analysis with SPSS 27 to test both the direct and indirect effects of marketing technology adoption on economic sustainability through market access. Findings: The results show that marketing technology adoption significantly improves both market access and farmers’ economic sustainability. Market access also demonstrates a strong positive effect on economic sustainability and partially mediates the relationship between technology adoption and sustainability outcomes. These findings indicate that digital marketing tools become more impactful when they successfully expand farmers’ access to broader and more competitive markets, rather than functioning as isolated technological interventions. Originality: The novelty of this study lies in its analytical approach, which incorporates market access as a mediating mechanism linking marketing technology adoption to farmers’ economic sustainability. Unlike previous studies that examine these variables separately, this research provides empirical evidence on how digital adoption translates into economic benefits through improved market connectivity among smallholder farmers. Research limitations: This study is limited to farmers in Nagrak District, with data collected solely through questionnaires. This may not fully capture deeper behavioral, contextual, and technological adoption dynamics. Practical implications: The findings highlight the importance of integrating digital marketing initiatives with efforts to broaden market linkages. For policymakers and farmer institutions, strengthening e-commerce readiness, market networks, and digital literacy programs can significantly enhance farmers’ bargaining power and long-term economic sustainability